Respostas
respondido por:
1
Bom, será raiz da equação, aqueles números que quando substituírem o x, deixarão a equação igual a zero. No caso o -2 e o 4.
Veja:
x² - 2x -8 = 0 [ x = -2]
(-2)² - 2(-2) - 8 = 4 + 4 - 8 = 0
-----------------------------------------------------------------------------------------------------
x² - 2x -8 = 0 [ x = 4]
(4)² - 2(4) - 8 = 16 - 8 -8 = 0
Veja:
x² - 2x -8 = 0 [ x = -2]
(-2)² - 2(-2) - 8 = 4 + 4 - 8 = 0
-----------------------------------------------------------------------------------------------------
x² - 2x -8 = 0 [ x = 4]
(4)² - 2(4) - 8 = 16 - 8 -8 = 0
Anônimo:
agora entendi.....valeu.....
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás